Portraiture in early India : between transience and eternity - Lefèvre, Vincent (Handbook of oriental studies. South Asia, 2011)
In the study of Indian art prior to the Mughal period, portraiture has so far been much neglected, when its existence has not simply been denied. This book is an attempt to reassess this issue, by showing that portraits have existed in great number in early India, since probably the first artistic achievements. Through a close scrutiny of sculpted and (more rarely) painted images brought together with textual and epigraphical references, it aims at highlighting the specificities of Indian portraiture, its relationship with divine images and, consequently, at understanding the development of In.